Properties, classification and suitability of Malaysian soils derived from granite-gneiss and potential of basalt to improve growth of rubber (Hevea brasiliensis Müll. Arg.) - Mokhatar, Mohd Shafar Jeffri (2017)
Soils planted with rubber in Malaysia are usually highly weathered soils and known as acidic soils, characterized by low fertility. Recently, the use of basalt to alleviate soil acidity has attracted soil scientists and agronomists in some parts of the world. This study was conducted to characterize soils developed on granite-gneiss and to evaluate the potential of ground basalt as soil amelioration in relation to growth and nutrition of rubber. The study area was located at Geliar, Jeli, Kelantan (05.70497° N, 101.80118° E). Six soil profiles at different slope position were identified, described and sampled, whereby the areas were already planted with immature rubber. Soils developed on very hilly terrain (20°-25°) and hilly (12°-20°) have better drainage and more weathered compare to soil developed on flat area (0°-2°). In terms of clay mineralogy, it is dominated by kaolinite, as shown in XRD diffractogram at reflections 7.2 Å, 3.58 Å and 3.4 Å, followed by gibbsite at 4.82 Å and 4.32 Å. Goethite (4.18 Å), haematite (2.69 Å and 2.51 Å), and quartz (3.3 Å) also detected in the soil profile. Feldspar (3.25 Å) and mica (10 Å) present in high water table soil profile as shown by weak peak in diffractogram. Pedon I, Pedon II, Pedon III and Pedon VI can be classified as Lanas Series Red Variant deep phase. Pedon V can be classified as Lanas Series deep phase (yellow) and Pedon IV can be classified as Local Alluvium Complex. According to USDA soil taxonomy, Pedon I, Pedon II, Pedon III, Pedon V and Pedon VI can be classified as fine clayey, kaolinitic, isohyperthermic, Typic Kandiudults. All soils on high sloping area can be classified as Haplic Acrisol (Clayic) according to World Reference Base for Soil Resources. Pedon IV situated on flat area can be classified as loamy, mixed, isohyperthermic, Fluvaquentic Endoaquepts and Gleyic Cambisol (Geoabruptic) according to Soil Taxonomy and World Reference Base for Soil Resources, respectively. For soil suitability classification for rubber cultivation, soils on Pedon I, Pedon II, Pedon III and Pedon VI can be categorized into Class III, while soil on Pedon V can be categorized into Class II and Pedon IV can be categorized into Class IV. From growth data collected, steeper area (25°) would be more favorable for rubber growth during immature stage. For nursery trial, two types of soil were selected from six profiles along catena. Both types of soil were subjected to different rates of ground basalt, 0, 40, 80, 160 and 240 g/polybag. The experiment was carried out as randomized complete block design (RCBD) with three blocks. The girth and height were measured for a year. After a year, soil chemical properties and nutrients in leaf tissue were analyzed. The results showed that incorporation of basalt at 240 g/tree had improved soil fertility. Increase of soil pH results in decreasing Al concentration. Basalt applications enhance growth of immature rubber in terms of height and girth. Nutrients content in the tissue also increased with basalt application and increases with increasing rate applied. Effect of ground basalt application on growth was evident after three months and continued to increase over time. This study shows that the logistic growth curve model in the form of y = A/ (1+be-ct) [where y and t were the plant parameters and months after transplanting, respectively, while A, b and c were regression constants] was biologically fit in describing the growth in terms of each of the parameters (stem girth and plant height) versus months after transplanting. At each ground basalt rate applied, the model had F value with high approximate probability level at α = 0.0001. For confirmation of study in nursery, a field trial was carried out. The experiment was carried out as complete randomized design (CRD), consisting of four rates of basalt (0, 179, 358 and 538 g/plant) and three replications. The field trial and the nursery have similar trend where application of basalt have enhanced fertility of the soil and growth of the rubber. Highest growth showed by plant with highest relative growth rate of height and girth with value of 16.76 cm/month and 0.681 cm/month respectively. Results showed that cation exchange capacity of the soil increased up to 22% and 45% with the application of 538 g/tree of basalt, after six months and a year. Basalt rate at 538 g/tree would be suitable to be used in field planting. From all data gathered in this study, it can be concluded that slope position influenced the soil formation, fertility, suitability and subsequently the growth of immature rubber tree. In order to improve fertility of highly weathered soils and enhancing early growth of rubber tree, ground basalt could be applied as a soil amendment in rubber plantation.